Developing a Sustainable Concrete using Waste Glass and Rubber for Application in Precast Pedestrian Slabs - Seeboo, Asish; Choollun, Chetanand (Civil Engineering Journal, 2021)
In this piece of research, n attempt was made to produce a sustainable concrete with the partial replacement of both fine and coarse natural aggregates with two different non-biodegradable wastes. The selected wastes were fine glass and shredded rubber tires. Fine glass passing through 4.75 mm BS sieve was utilised for the partial replacement of fine natural aggregates. Coarse natural aggregates were partially replaced with shredded rubber passing through 20 mm sieve and retained on 6.30 mm sieve. Several mixes with varying % of fine glass but with a fixed 10 % of shredded rubber were tested. Optimum fine glass content was determined to be in the order of 20 %. The resulting concrete exhibited lower plastic and hardened densities (2040 and 2117 kg/m3 respectively) in comparison to normal plain concrete. The static modulus of elasticity was found to be 18.3 GPa (mean value), while the splitting tensile strength was 2.37 MPa. The flexural strength showed a significant increase of 20.3% compared to the control mix. The results concluded that the concrete thus produced is a viable means of disposing of such non-biodegradable wastes (rubber and glass), thus reducing the loads at landfills. This new genre of concrete was produced at a lower cost than normal concrete because of the very low pre-treatment costs of the recycled wastes used. Furthermore, the properties tend to indicate that the concrete could be applied where lower strength and high durability properties are warranted. Hence precast slabs were made from the new design concrete and were tested along a stretch of a highly trafficable pedestrian walkway on the University campus. The slabs were continuously monitored for defects such as cracks, broken corners and slabs for a period of 24 consecutive weeks. After the test period it was observed that only 4 out of the 80 precast slabs had hairline cracks. Hence concluding the enhanced durability properties of the new design concrete.Â Doi: 10.28991/cej-2021-03091690 Full Text: PDF